2010
DOI: 10.1111/j.1365-2249.2010.04159.x
|View full text |Cite
|
Sign up to set email alerts
|

T cell response to viral antigens in adults and children with common variable immunodeficiency and specific antibody deficiency

Abstract: SummarySeveral T cell abnormalities have been described in common variable immunodeficiency (CVID), a B cell disorder of mainly unknown origin. A subset of CVID patients suffers from frequent reactivations of herpes viruses. We studied T cell function in CVID [and in a subset of paediatric patients with specific antibody deficiency (SAD)] by measuring T cell proliferation and cytokine production in response to herpes virus-antigens in paediatric CVID patients (n = 9) and paediatric SAD patients (n = 5), in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…Furthermore, in our study we observed the same frequencies of HHV‐6‐specific CD4+ T cells regardless of presence or absence of HHV‐6 DNA in blood. Similarly, CD4+ T cell proliferation in response to HHV‐6 in pediatric patients with common variable immunodeficiency is comparable to that observed in controls .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Furthermore, in our study we observed the same frequencies of HHV‐6‐specific CD4+ T cells regardless of presence or absence of HHV‐6 DNA in blood. Similarly, CD4+ T cell proliferation in response to HHV‐6 in pediatric patients with common variable immunodeficiency is comparable to that observed in controls .…”
Section: Discussionsupporting
confidence: 54%
“…In patients with common variable immunodeficiency, the pro‐inflammatory cytokines IL‐6 and TNF‐α are produced in response to stimulation with HHV‐6 antigens. Overall, no major differences between patients and controls in cytokine production upon stimulation were detected . Moreover, an increase in IL‐6 production has been demonstrated in patients with HHV‐6 infection in previous studies , whereas another study reported strong of production TNF‐α, but not of IL‐6, by PBMCs from healthy donors stimulated with HHV‐6 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…T cell responses have been reported to be higher in HSCT patients [42], but few studies have focused on this population. Despite the low frequency of responding T cells in healthy adults, strong CD4+ and CD8+ T cell proliferative responses are observed [4345], primarily restricted to memory cells. Proliferation of HHV-6-specific T cells in response to viral antigen allows these low-frequency T cell populations to be expanded in vitro for detailed study.…”
Section: T Cell Responsesmentioning
confidence: 99%
“…There is the possibility that these uncommon patients have an autosomal recessive form of combined immune deficiency since there is an over-representation of consanguinity in this group [14]. There are reports of defects of antigen presentation and cellular immunity in CVIDs and at least half of patients with CVID have circulating T cells specific for epitopes derived from CMV and/or EBV [15, 16]. Whether this is relevant to the development of MALT lymphomas in CVID patients remains to be seen.…”
Section: Introductionmentioning
confidence: 99%